2018
DOI: 10.1177/1533033818797587
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Study on Attenuating Angiogenesis and Epithelial–Mesenchymal Transition (EMT) of Non-Small Cell Lung Carcinoma (NSCLC) by Regulating MAGEC2

Abstract: Objective:To investigate the role of MAGE family member C2 in angiogenesis and epithelial–mesenchymal transition of non-small cell lung carcinoma.Methods:The Cancer Genome Atlas data set was analyzed to filter the highly expressed gene melanoma antigen family C2 in non-small cell lung carcinoma. Quantitative reverse transcription-polymerase chain reaction was performed to verify the overexpression of melanoma antigen family C2 in non-small cell lung carcinoma cell lines. Melanoma antigen family C2 complementar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Further IHC analyses in clinically invasive and metastatic HCC samples also suggested that MAGEC2 promoted HCC invasion and metastasis via EMT. Similarly, Jiang et al25 recently reported that MAGEC2 upregulated the expression of EMT-related proteins and enhanced growth and metastasis in NSCLC; Chen et al29 stated that MAGEC2 facilitated colony formation and migration by inducing the EMT of tumour cells in oesophageal squamous cell carcinoma; Yang et al30 described that MAGEC2 acted as an EMT inducer and was dramatically associated with breast cancer metastasis. Our present results are consistent with previous studies on the EMT-promoting role of MAGEC2 in human cancers.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Further IHC analyses in clinically invasive and metastatic HCC samples also suggested that MAGEC2 promoted HCC invasion and metastasis via EMT. Similarly, Jiang et al25 recently reported that MAGEC2 upregulated the expression of EMT-related proteins and enhanced growth and metastasis in NSCLC; Chen et al29 stated that MAGEC2 facilitated colony formation and migration by inducing the EMT of tumour cells in oesophageal squamous cell carcinoma; Yang et al30 described that MAGEC2 acted as an EMT inducer and was dramatically associated with breast cancer metastasis. Our present results are consistent with previous studies on the EMT-promoting role of MAGEC2 in human cancers.…”
Section: Discussionmentioning
confidence: 90%
“…Ki67 expression in nude mice was examined, and the results demonstrated that Ki67 expression was significantly reduced after MAGEC2 knockdown, which further implied the facilitating role of MAGEC2 in tumour growth. Similarly, Bhatia et al23 showed that MAGEC2 promoted tumour growth and tumourigenicity in melanoma; Hao et al24 revealed that MAGEC2 overexpression increased the G1-S transition and cell proliferation in multiple kinds of cancer, including colorectal cancer, cervical cancer, breast cancer and melanoma; Jiang et al25 stated that MAGEC2 promoted proliferation, migration, and invasion and suppressed apoptosis in non-small cell lung carcinoma (NSCLC) cell lines, and MAGEC2 could also facilitate tumour growth and metastasis in NSCLC xenografts.…”
Section: Discussionmentioning
confidence: 97%
“…SSX2 interacts with Rab3IP to promote EMT [22]. MAGEC2, which is highly expressed in non-small cell lung cancer cells, promotes angiogenesis and EMT [23]. MAGE-A3 shows high expression in cervical cancer cells and promotes cancer cell metastasis by activating Wingless-related integration site (Wnt) signaling [24].…”
Section: Of 26mentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT) and angiogenesis are two critical components that support tumor growth and metastasis in the tumor microenvironment ( Jiang et al, 2018 ). EMT, a process in which epithelial cells transform phenotypically into mesenchymal cells, lose their adhesive properties and cell-cell contacts and gain migration properties, has been shown to play an important role in cancer metastasis ( Suda et al, 2017 ; Li et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%